Clinical and genetic characteristics in patients with Huntington's Disease from Argentina - Gatto, Emilia Mabel (2012)
Huntington's Disease (HD) is a neurodegenerative disease, caused by the expansion of an unstable (CAG) n in the HTT gene. There is scarce data about the disease in Argentina. Objective: To describe the demographic, clinical and molecular data in patients with HD from Argentina. Patients and methods: 59 HD patients were recruited at our department.Comprehensive interviews, neurological examination and genetic analysis were performed in probands. Statistical analysis was conducted using G-Stat 2.0 and non-parametric tests (Wilcoxon). Results: 32 women and 27 men were diagnosed with a mean age of 45.7±16.2years and a mean age at onset of 35.8±14.8years. We found no gender prevalence and an inverse correlation between size of mutant CAG repeat sequence and age at onset, r=-0.58, r 2=33.6, Pearson's correlation coefficient p=0.0008.Juvenile HD in this series of patients was higher than previously reported (16.6% vs. <10%). The mean CAG repeat in the expanded allele was 45.1. The number of CAG repeats in Argentinean controls was 17.8, which is similar to the literature of the European population. Conclusions: This is the first series of Argentinean HD patients with demographic, clinical and molecular data. Our findings appear similar to the ones described in Western European populations.